AB0646 IS IT FEASIBLE TO ACHIEVE RECOMMENDED THERAPEUTICAL TARGET IN PATIENTS WITH AXIAL SPONDYLARTHRITIS IN CLINICAL PRACTICE? DATA FROM THE SpA-Paz COHORT. (2nd June 2020) - Franco Gomez, K. N.; Plasencia, C.; Novella-Navarro, M.; Benavent, D.; Bogas, P.; Nieto, R.; Monjo, I.; Nuño, L.; Villalva, A.; Peiteado, D.; Balsa, A.; Navarro-Compán, V.
Abstract : Background: Current ASAS/EULAR recommendations for the management of patients with axial spondylarthritis (axSpA) establish that the therapeutic goal to achieve in clinical practice is remission, defined as the absence of both clinical and laboratory disease activity evaluated by BASDAI&CRP or preferably ASDAS and if this is not possible, low disease activity may be an alternative. Recently, ASDAS nomenclature has been modified, calling now low disease activity to what was previously called moderate activity. To this day we do not know if this target is feasible in clinical practice. Objectives: To analyze the frequency of patients with axSpA achieving maintained remission (R) or low disease activity (LDA) after receiving biological therapy. Secondary objectives included: i) to assess if the activity index used influences the frequency of maintained R/LDA, ii) analyze the prognostic factors for achieving maintained R/LDA. Methods: An observational, longitudinal study of a prospective cohort (SpA-Paz) including all patients with axSpA who initiated their first biological treatment between the years 2003-2017. Demographic, clinical and analytical data were collected at the beginning of treatment and clinical disease activity measured by BASDAI&CRP and ASDAS every 6 months for 2 years. Maintained R was defined as (BASDAI<2 & normal CRP and/or ASDAS <1.3) and maintained LDA (BASDAI <4 & normal CRP and/or ASDAS <2.1) on at least 3 consecutive visits. Statistical analysis: i) measures of central tendency and dispersion for quantitative variables and frequencies for qualitative variables; ii) univariate and multivariate analysis of binomial logistic regression model and calculation of OR and 95% CI. Results: Out of 186 patients with axSpA who started treatment during the study period, 63% were men with a mean age of 54 ± 14.1 years. 75.3% of the patients had radiographic axSpA and 74.7% were HLA-B27 positive. Other baseline characteristics (not shown due to space restrictions). Overall, 80% of the patients achieved ASDAS R/LDA (R36%/LDA44%) in at least one of the visits after 2 years of follow-up, but only 40% (R27%/LDA13%) fulfilled the maintained ASDAS R/LDA state. On the other hand, 73% of patients were classified as BASDAI&CRP R/LDA (R31%/LDA42%) in at least one of the visits, but only 31% (R21%/LDA10%) obtained the maintained BASDAI&CRP R/LDA state. In the multivariate analysis, we observed an independent statistically significant association with male sex (OR=3.19; 95% CI=1.46-6.99), younger age at the beginning of the biological treatment (OR=0.97; 95% CI=0.95-0.99) and the use of methotrexate (OR=3.07; 95% CI=1.39-6.78) in patients who achieved maintained BASDAI&CRP R/LDA and with male sex (OR=4.01; 95% CI=1.83-8.77), younger age at the beginning of the biological therapy (OR=0.96; 95% CI=0.94-0.99) and HLA B27 presence (OR=4.30; 95% CI=1.68-11.01) in patients who achieved maintained ASDAS R/LDA. Conclusion: Although the majority of patients with axSpA who initiate biological therapy achieve the recommended therapeutic goal in the first two years of treatment, the percentage of patients who manage to maintain the R/LDA status is limited. In our study, maintained R was more frequent than maintained LDA, being somewhat higher when measured by ASDAS. This fact may suggest that patients who achieve maintained R have a greater inhibition of their inflammatory activity and, therefore, it remains in time. Male sex and younger age at the beginning of the biological therapy were the main baseline predictors for achieving maintained R/LDA. Graphics: Disclosure of Interests: Karen Nathalie Franco Gomez: None declared, Chamaida Plasencia: None declared, Marta Novella-Navarro: None declared, Diego Benavent: None declared, Patricia Bogas: None declared, Romina Nieto: None declared, Irene Monjo: None declared, Laura Nuño: None declared, Alejandro Villalva: None declared, Diana Peiteado Grant/research support from: AbbVie, Lilly, MSD, and Roche, Speakers bureau: AbbVie, Roche, and MSD, Alejandro Balsa Grant/research support from: BMS, Roche, Consultant of: AbbVie, Gilead, Lilly, Pfizer, UCB, Sanofi, Sandoz, Speakers bureau: AbbVie, Lilly, Sanofi, Novartis, Pfizer, UCB, Roche, Nordic, Sandoz, Victoria Navarro-Compán Consultant of: Abbvie, Lilly, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, MSD, Lilly, Novartis, Pfizer, UCB